On the issue of low adherence of patients to antihypertensive therapy: the use of therapeutic drug monitoring of drugs: A review - Marina V. Leonova (ZAO "Consilium Medicum", 2022)
Low adherence of patients to antihypertensive therapy remains an urgent problem and is recognized as the main cause of insufficient BP control at the population level. In this regard, to increase the motivation of patients in clinical practice, methods for assessing adherence (compliance) to drugs. Along with indirect assessment methods (questionnaires, self-reports, pill counts, etc.), which, however, do not always reflect the real patients adherence, more objective is the measurement of antihypertensive drug concentrations in physiological fluids therapeutic drug monitoring (TDM). For these purposes, methods of high-performance liquid chromatography with mass spectrometry were recently adapted, reference ranges of antihypertensive drug concentrations in blood serum and urine for standard doses of drugs were determined, as well as criteria for assessing complete or partial non-compliance. There have been a number of studies using TDM to assess adherence, which show a high rate of non-compliance (low compliance) of more than 50% of cases with a variability from 25 to 86.1%, with complete non-compliance 10.134.5% in patients with uncontrolled and/or resistant hypertension (3 antihypertensive drug). In a population of patients with a normal course of hypertension, taking 12 antihypertensive drug, the level of non-compliance according to the results of TDM did not exceed 10%. Comparison of the TDM method with indirect methods of assessing adherence did not reveal consistency; at the same time, the detection of antihypertensive drug better characterized the clinical problems of patients with arterial hypertension. In clinical practice, direct assessment methods (TDM) can be used to measure adherence in problem patients with uncontrolled hypertension and high cardiovascular risk despite optimal therapy.